Deriving active database triggers from business rules model with conceptual graphs - Valatkaitė, Irma; Vasilecas, Olegas (Lietuvos matematikos rinkinys, 2002)
ECA rules implemented into database management systems (DBMS) as triggers have proven to be powerful and effective mechanisms to enforce business rules in applications. Collection of all business rules implemented in united repository of specific DBMS reduces efforts of implementation and maintenance, so does uniform domain conceptual model. Several conceptual modelling languages might be used but we propose to use conceptual graphs (CGs) because CGs offer constructs for modelling all static and dynamic aspects of application domain in a uniform way, and have both, a standard representation, and a graphical notation. In this paper we propose a generic algorithm to generate database triggers from domain model represented by CGs. The algorithm uses Conceptual Graphs Interchange Format (CGIF) representation. Such usage of CGs for business rules modelling is advocated.